Problematika dan Tantangan Pembelajaran Pendidikan Agama Islam di Tengah Pandemi Covid-19 - Suherman, Herman (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2020)
At this time all countries in the world are being hit by a major disaster caused by the Covid- 19 virus. Covid-19 virus is apparently having an impact in the world of education is no exception to the learning of Islamic religious education. In an emergency such as this Islamic religious education learning still has a very important role for students when facing the Covid-19 pandemic. Because in essence the aim of learning Islamic religious education is to increase the faith, understanding, appreciation and practice of students about Islam so that they become Muslim people who believe and have the piety of Allah SWT and have good character in their private lives, in society, nation and state. The purpose of this study is to identify the problematics of Islamic religious education learning in teaching and learning activities online (in networks) during the Covid-19 pandemic. This research uses the field research method (Field Research) and uses a descriptive qualitative approach. The data collection techniques used in this study were interview and observation. While the data analysis in this study uses qualitative data that is presented without calculation of numbers. The respondents of this study were one of the homeroom teachers and class.